Steps towards Man. Contribution to a Neo-criticistic Reading of Evolutionary Psychology (Nóema, 2018)
The article aims to examine Michael Tomasello's research in evolutionary psychology from the point of view of Cassirer's neo-criticism. The analysis will highlight, in a general context as well as in reference to a specific case taken from Tomasello, how evolutionary psychology is better understood, thanks to a trascendental analysis of its main concepts, as a composite discipline, endowed with different development levels.
Keywords: Tomasello; Cassirer; evolutionary psichology; neo-criticism